Use of Oil Palm Frond and Palm Oil Sludge in Total Mixed Ration on Productive Performance of Finishing Goat - Seephueak, Wuttichai; Ngampongsai, Wanwisa; Wattanachant, Chaiyawan (Princess of Naradhiwas University Journal, 2019)
The objective of the experiment was to determine feed intake, digestibility, productive performance and feed cost in total mixed ration of finishing goat. A randomized completed block design 2X2 factorial design was used. Factor were breeds (Thai native-Anglo Nubian, Thai native-Boer) and fiber sources in total mixed ration (OPF+POS, hay). The result shown that the goats received OPF+POS were higher feed intake at%body weight and g/metabolic weight than hay (p<0.05). Breeds and fiber sources were not affected on average daily gain and feed/gain (p>0.05). Goats received OPF+POS were higher digestion coefficient such as protein, organic matter, acid detergent fiber and neutral detergent fiber than hay (p<0.01. Net profit with accounted for only feed cost/weight gain were similar in both breeds. However, goats received OPF+POS were higher net profit with accounted for only feed cost/weight gain than hay.